External beam radiation therapy versus radical prostatectomy for high-risk prostate cancer: protocol of the RECOVER study - Caroline M. van der Starre; Chris H. Bangma; Maarten J. Bijlsma; Alfons C.M. van den Bergh; Lambertus A.L.M. Kiemeney; Wietske Kievit; Kees Vos; Diederik M. Somford; Sally M. Wildeman; Katja K.H. Aben; Igle J. de Jong; Floris J. Pos; et al. (BMC Cancer)
Abstract Background This paper describes the rationale and design of the RECOVER study. Currently, there is no consensus regarding the optimal treatment for high-risk, non-metastatic prostate cancer (PCa). The study primarily aims to evaluate and compare the impact of treatment with robot-assisted radical prostatectomy (RP) versus external beam radiation therapy (EBRT) with androgen deprivation therapy (ADT) for men with high-risk, non-metastatic PCa regarding health-related quality of life (HRQoL) and functional outcomes. Secondary objectives are progression-free survival (PFS), distant metastasis-free survival (DMFS), costs and cost-effectiveness. Methods The RECOVER study is a comparative effectiveness study that prospectively includes newly diagnosed high-risk (cT3a-bN0M0, ISUP-grade ≥ 4 and/or PSA > 20 ng/mL), non-metastatic PCa patients. Four Dutch prostate cancer networks, comprising 29 hospitals, are currently participating in the study. Patient reported outcomes are collected before treatment initiation, 12 months and 36 months after treatment initiation and include the EORTC-QLQ-C30, the EPIC-26, an adapted version of the SCQ, an adapted version of the iMTA Productivity Cost Questionnaire and several specific questions regarding patient characteristics, treatment of PCa specific complaints and health resources used. Clinical data regarding patient-, tumor- and treatment characteristics and oncological outcomes are collected up to 5 years after diagnosis. For sufficient power, patient reported outcomes of 471 patients must be collected 36 months after treatment initiation. Descriptive statistics and mixed-effects models are used to assess differences in HRQoL and functional outcomes over time between the patients treated with radical prostatectomy versus EBRT (+ ADT). Inverse probability of treatment weighting or the g-formula are used to adjust for confounding covariates associated with treatment. Secondary endpoints PFS and DMFS are evaluated using a competing risk analysis and cost-utility and budget-impact analyses will be performed to determine cost and cost-effectiveness. Discussion An observational prospective design was chosen since a randomized controlled trial comparing surgery and radiotherapy was not deemed feasible. This study evaluates effectiveness of treatment in a routine clinical setting (with adjustment for confounding) and its findings will enhance patients’ and healthcare professionals’ awareness for the impact of both treatment modalities on (long-term) daily functioning and HRQoL and aid treatment decision making. Trial registration This study is registered at ClinicalTrials.gov (NCT05931419).